Integrating SDGs into Sustainable Development in the Coastal Areas of Sumatra Island: A Case Study in Bengkalis Regency - Taryono Taryono (FKIP, Universitas Palangka Raya, 2024)
This research examines effective methods for integrating Sustainable Development Goals (SDGs) into sustainable development in coastal villages on Sumatra Island, particularly in Bengkalis Regency. By employing both qualitative and quantitative approaches, the study aims to understand the challenges and opportunities faced by these villages. Coastal villages in Bengkalis show varying development statuses, with some reaching a level of self-sufficiency while others need further support to advance. The 2023 Village Development Index (IDM) reveals significant differences in SDG achievements, highlighting the need for targeted strategies. Recommendations include enhancing community capacity through training, empowering women, and involving local communities in program planning and implementation. Prioritizing environmentally friendly infrastructure and sustainable technologies is essential to address issues of consumption, production, and climate change. Additionally, supporting inclusive economic growth and poverty reduction through skills training and small enterprise support is crucial. Strengthening partnerships between local governments, the private sector, and non-governmental organizations will facilitate effective coordination and resource allocation. A comprehensive monitoring and evaluation system is needed to assess and adjust policies, ensuring improved sustainable development outcomes for Bengkalis Regency..